Toward the enhanced effectiveness of foreign aid - Gustav Ranis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
At the very time that professional skepticism concerning the effectiveness of foreign aid has reached new heights, donors seem to be ready to substantially increase the volume of aid they are willing to make available. This paper attempts to address this paradox by first examining the record of aid in the past, distinguishing between crosscountry regressions and select country experience. It subsequently proceeds to propose the establishment of a new modus operandi for foreign aid, based on a much more passive, bankerlike posture by donors, leaving the initiative for defining what reforms are feasible, plus the establishment of self-conditionality, to third world recipients before they approach the international community of donors.
Keywords: O11; O19; 330; foreign aid; development; Entwicklungshilfe; Entwicklung